Principles and Psychological Approach of Working with Problem Students of Teaching Staff in the Higher Education System - Lazokat Eshimbaevna Izaitullaeva (Open Academia, 2023)
This article examines the principles and psychological approaches of pedagogical personnel in the higher education system to work with problematic students.
Keywords: Pedagogical leader; social adaptation